Stres psikologis dengan kejadian gastritis pada narapidana di sukadana, Lampung - Rahma Elliya; Leni Haryanti (Holistik Jurnal Kesehatan, 2020)
Psychological stress in gastritis occurrence among prisoners at sukadana, LampungBackground: Based on Indonesia's health profile in 2011, gastritis is one of the 10 most common diseases in hospitalized patients in Indonesia with 30,154 cases (4.9%). Based on data from the monthly repor ts of non-communicable diseases, it was known that in December 2018 the most common diseases were 12 people with digestive disorders followed by 2 people with respiratory diseases and 2 people with dental diseases.Purpose: To identify psychological stress in gastritis occurrence among prisoners at sukadana, LampungMethod: A quantitative research, analytic survey research design with cross sectional approach). The population in this study were all residents of detention in class II B Sukadana prison. Independent variable: stress. Dependent variable: gastritis availability. Collecting data with questionnaires and medical records. It is planned to be conducted in March - April 2019. Analysis of data is univariate (frequency distribution) and bivariate using the chi square test.Results: It was known by respondents with the incidence of gastritis, as many as 130 (60.5%) respondents were gastritis and as many as 85 (39.5%) respondents were not gastritis. It was known by respondents with the incidence of stress, as many as 111 (51.6%) respondents were stressed and as many as 104 (48.4%) respondents were not stressed. There is a relationship between stress and the incidence of gastritis in prisoners (p-value = 0,000 OR = 9,012). Suggestions provide information to respondents regarding factors that influence the incidence of gastritis, especially stress.Conclusion: There is a relationship of Stress with the incidence of gastritis in inmates in Sukadana. Suggestions provide information to respondents regarding factors that influence the incidence of gastritis, especially stress.Keywords: Psychological stress; Gastritis occurrence; PrisonersPendahuluan: Gastritis menjadi salah satu penyakit dari 10 penyakit terbanyak pada pasien inap di rumah sakit di Indonesia dengan jumlah 30.154 kasus (4,9%). Berdasarkan data dari laporan bulanan penyakit tidak menular diketahui pada bulan Desember 2018 penyakit terbanyak adalah gangguan pencernaan sebanyak 12 orang diikuti penyakit pernapasan sebanyak 2 orang dan penyakit gigi sebanyak 2 orang.Tujuan: Diketahui hubungan stres dengan kejadian gastritis pada narapidana di Sukadana.Metode: Penelitian kuantitatif, rancangan penelitian survei analitik dengan pendekatan cross sectional). Populasi dalam penelitian adalah seluruh penghuni rumah tahanan di lapas kelas II B Sukadana . Variabel independen: stress. Variabel dependen: kejadian gastritis. Pengumpulan data dengan kuesioner dan rekam medik. Telah dilakukan pada bulan Maret – April 2019. Analisa data secara univariat (distribusi frekuensi) dan bivariat menggunakan uji chi square.Hasil: Diketahui responden dengan kejadian gastritis, sebanyak 130 (60,5%) responden gastritis dan sebanyak 85 (39,5%) responden tidak gastritis. Diketahui responden dengan kejadian stress, sebanyak 111 (51,6%) responden stres dan sebanyak 104 (48,4%) responden tidak stress. Ada hubungan antara stres dengan kejadian gastritis pada narapidana (p-value = 0,000 OR = 9,012).Simpulan: Ada hubungan Stres dengan kejadian gastritis pada narapidana di rumah tahanan Negara klas II B Sukadana. Saran memberikan informasi kepada responden terkait faktor yang mempengaruhi kejadian gastritis khususnya stres.